Levantamento de potencial hidroenergético na bacia do Paraná 3 utilizando geotecnologias - Wegner, Newmar (2018)
The need to obtain information to geolocate potential areas to install Hydroelectric Generating Centers (GHGs) and Small Hydroelectric Powerplants (PCHs) is increasing in Brazil, considering the growth of energy demand is constant and the choice of using clean technology to produce energy is encouraged by the Government. In this context, this researched aimed to investigate the potential areas to install these powerplants in the river Paraná Basin 3, in order to obtain the possibility for energy production from identified potential points in the mains rivers in the basin (considering slopes vs. flow features). In Paper 1, the flow data parameterization (made available by the Brazil National Water Agency) was performed to generate multiple regression models to estimate the flow in several points of the main watercourses of the Paraná Basin 3. Automated procedures were created and applied using geoprocessing software and R statistic to obtain morphometric characterization of watersheds, two multiple regression models were obtained for flow estimation in the Paraná Basin 3, considering both dry and rainy periods, presenting coefficients of determination R2 of 87 and 86%, respectively. In Paper 2, it was possible to evaluate and estimate the potential for energy production in the region, considering environmental variables and legislation for implementing, thus geolocating the areas of high interest to carry out this study. The procedures allowed to estimate the potential for river segment generation with 450-meter sections (at 3,899 points) in the Paraná Basin 3, identifying its energy potential, considering the definition of priority areas for the implementation of these projects as well as environmental and legislative feasibility. This analysis resulted in 3,477 analyzed points for the implantation of CGHs (up to 3 MegaWatts) and 48 potential points of PCHs (between 3 and 30 MegaWatts).